THE USE OF QUIZIZZ TO IMPROVE ENGLISH VOCABULARY MASTERY AMONG EFL ELEMENTARY SCHOOL STUDENTS IN SETU BABAKAN AREA - Muhamad Dhion Fardhansyah (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
This research analyzes whether or not the use of Quizizz is beneficial in expanding the vocabulary of elementary school students. In this inquiry, a quantitative approach to the pre-experiment phase is taken. The purpose of this research is to investigate whether or not the use of Quizizz as a learning aid to boost students' vocabulary is effective. The number of pupils from elementary schools in the area around the Betawi cultural hamlet who took part in the exciting activities that were planned for the course was used to determine the number of samples that were collected. There were a total of twenty children that took part in the activity known as the Fun Course. In order to evaluate the students' ability to respond appropriately to vocabulary questions, the researcher gave them both a pre-test and a post-test. The results of the post-test that were given to students in elementary school suggest that having access to Quizizz makes a substantial difference in improving their overall performance on the exam. On the pre-test, the average score was 69, whereas on the post-test, the average score was 89.8. On the basis of these differences, it is possible to draw the conclusion that the primary students' command of the English language has greatly improved.